Use of bone landmarks for assessing the safety of acupuncture on the posterior midline of the neck region - Zhiliang Tang; Jiao Liu; Jin Li; Chunming Ma (BMC, 2024)
Abstract Objective Many acupuncture acupoints are located on the posterior midline of the neck region. The needling depth for acupuncture is important for practitioners, and an unsafe needling depth increases the possibility of damage to the spinal cord and brainstem. Can the safety of acupuncture be assessed by examining bone structures? We focused on this aim to carry out this study. Methods The shortest distance from the posterior border of the foramen magnum to the line joining both upper ends of the posterior border of the mastoid process was measured on 29 skulls. Distances from the posterior border of the vertebral foramen to the tip of the spinous process and posterior tubercle of the atlas were measured and evaluated from 197 dry cervical vertebrae and 31 lateral cervical radiographs of patient subjects. The anatomic relationships of the vertebral canal with the external occipital protuberance, tip of the spinous process of the axis, tip of the posterior tubercle of the atlas, and upper end of the posterior border of the mastoid process were observed and evaluated via lateral cervical radiography. Results The shortest distance from the foramen magnum to the line between the mastoid processes was 4.65±1.75 mm, and the distance from the superior border of the vertebral foramen of the atlas to the posterior tubercle was less than the distance from the inferior border. The distance from the superior border of the vertebral canal to the tip of the spinous process in C2-C7 was greater than the distance from the inferior border. The mean lengths of the superior border of the C2 spinous process and the inferior border of the C7 spinous process were greater than 21 mm and 31 mm, respectively. The line from the upper end of the posterior border of the mastoid process to the tip of the C2 spinous process or 10 mm deep to the tip of the C2 spinous process was posterior to the vertebral canal. Conclusions On the posterior midline of the neck region between the tip of spinous process of axis and external occipital protuberance, if the needle reaches the depth of the line between the upper end of posterior border of mastoid process and the tip of the spinous process of the axis, approximately 10 mm along the spinous process of the axis, the needle is in the safe region. The mean length of the C2-C7 spinous process is suitable to accommodate the needling depth of the adjacent acupoint. Bone structures can be used to effectively assess the safety of acupuncture on the posterior midline of the neck region.